Força pra subir, coragem na descida: um estudo sobre as resistências das meninas na Fundação CASA - Grillo, Nathalí Estevez (2018)
This study refers to getting to know the conditions in which the girls experience the social-educational measure of detention in order to expose the opressions suffered by them, in the context of an institution as Fundação CASA (Adolescent Social-Educational Attendance Center), depicting how they inhabit CASA Chiquinha Gonzaga as to identify the resistance tactics of the female adolescents who are deprived of freedom. The insertion as a professional through Projeto Guri at CASA Chiquinha Gonzaga – the largest female social-educational center in the state and the only one that holds the attendance program for mothers and their babies (PAMI) constituted as a research field where observations were made from the time spent together and the description of developed activities added to interviews with three teenage girls who have already finished the detention measure. The research draws its inspiration from the participatory action research methodology and also from the feminist methodology and sets off from theoretical frameworks such as critical criminology, the intersectionality of black feminism and affectivity as source of knowledge. The resistance tactics were debated through the axes of musicalitys, materialitys and affections around